Effect of thermal activity on critical heat flux enhancement in downward-hemispherical surface using graphene oxide coating. (December 2018) - Lee, Min Ho; Heo, Hyo; Bang, In Cheol
Highlights: Surface characteristics of the graphene oxide coating and its effect on critical heat flux were studied. Main enhancement mechanism was explained as increased thermal activity. Bubble behavior near the critical heat flux and after critical heat flux was visualized. Abstract: Critical heat flux (CHF) enhancement is needed to ensure a proper safety margin for the in-vessel retention through external reactor vessel cooling (IVR-ERVC), which is a decay heat removal strategy in the nuclear power plants. To enhance the cooling capability of IVR-ERVC, graphene oxide (GO) was coated on a boiling surface, with a reduced geometry to that of the reactor pressure vessel (RPV). This study experimentally investigated the effect of the GO coating on the CHF. A R-123 refrigerant was used as a working fluid to mitigate the wetting effect. Various concentrations of nanofluids were used in the experiments (0.01, 0.03, and 0.05 vol%) to examine the effect of thermal activity on the CHF. Because the thermal effusivity of the GO coating layer was higher than that of the copper heater, the thermal activity of the surface increased with thicker GO coating layers. The CHF limit of the GO-coated surface was enhanced by 38% compared to that of the bare surface due to increased thermal activity. Periodic bubble behavior was also observed near the CHF and visual criterion for CHF observation is detailed herein.